Pengaruh Intervensi Coping Mechanism Terhadap Stres Akademik Mahasiswa Tingkat Akhir (Studi Kasus Pada Mahasiswa Fakultas Ilmu Tarbiyah dan Keguruan Semester VIII di IBN Tegal Tahun Akademik 2024/2025) - Efvelin Barus; Akhmad Muzakki (Postgraduate University of Mataram, 2025)
This study aims to determine the level of academic stress, the coping mechanisms used, and the effect of coping mechanism interventions on the academic stress of eighth-semester students at FITK IBN Tegal. This study uses a quantitative method with a case study approach as a complement. The sample size was 31 students from a total population of 125 people selected using accidental sampling. Data analysis was conducted using simple linear regression with the assistance of SPSS version 24. The results of the study indicate that both academic stress levels and coping mechanisms fall into the moderate category. There is a significant influence between coping mechanisms and academic stress (p = 0.039 < 0.05) with a negative regression coefficient of -0.338, indicating that an increase in coping mechanism interventions is correlated with a decrease in academic stress levels. The coefficient of determination (R²) value of 0.139 indicates that coping mechanisms contribute 14% to academic stress. This finding highlights the importance of strengthening coping strategies in supporting the mental health of students in their final year of study.